RETRACTED: LncRNA BLACAT1 Accelerates Non-small Cell Lung Cancer Through Up-Regulating the Activation of Sonic Hedgehog Pathway - Sun, Jiwei; Jia, Jingzhou; Yuan, Wuying; Liu, Shu; Wang, Wei; Ge, Lili; Ge, Liyue; Liu, Xiao-Jun (Frontiers in Oncology, 2021)
Recently, increasing evidence has displayed that lncRNAs can exhibit crucial function in cancer progression, including lung cancer. LncRNA bladder cancer-associated transcript 1 (BLACAT1) is reported to participate in various cancers. The aim of our current study was to investigate the function of BLACAT1 in non-small cell lung cancer progression and study the functional pathway. Here, we reported BLACAT1 was significantly up-regulated in lung cancer tissues in comparison to the adjacent normal tissues，which suggested BLACAT1 might act as an oncogene in lung cancer. Then, A549 and PC9 cells were infected with BLACAT1 overexpression plasmid and shRNA. As shown, we proved up-regulation of BLACAT1 greatly induced the growth of non-small cell lung cancer cells. Reversely, knockdown of BLACAT1 reduced A549 and PC9 cell proliferation, migration and invasion. Sonic hedgehog (shh) signaling is able to exert a significant role in carcinogenesis, including lung cancer. Currently, we proved that up-regulation of BLACAT1 activated shh signaling pathway, via inducing shh, Gli-1 and Smo expression. shh pathway inhibitor GANT-61 reversed the effect of overexpression of BLACAT1 on non-small cell lung cancer. Moreover, we manifested that loss of BLACAT1 remarkably reduced the in vivo growth and metastasis of A549 cells via enhancing infiltrating CD3+ T cells. In conclusion, our research revealed a critical role of BLACAT1 in the modulation of non-small cell lung cancer via modulating shh pathway.